Using Quizizz in Learning Assesment with Science Literacy Oriented in Science Learning - Agustia, Mela; Aprilia, Charolin; Sari, Jenni; Hikmah, Darul; Risnita, Risnita (International Journal of Engineering, Science and Information Technology, 2021)
In the covid-19 era, activities are forced to be done from home, including learning activities. Because of the limited network, students' interest in doing assignments becomes low. Thus teachers tend to ignore the assessment of learning outcomes during the pandemic. Even though assess learning outcomes is very important to do, one of them is a daily test which aims to find out the extent to which students understand the lesson. This study aims to determine the use of the Quizizz applicationwith science literacy oriented as a media for assessing learning outcomes during the study. The research method used is applied research, namely by implementing the Quizizz application in science literacy for online assessment. The data collection method used was a questionnaire. Quantitative data collection was obtained with closed questions. Questionnare is given after students doing daily tests using Quizizz with science literacy oriented. The daily test consists of 20 multiple choice questions of Motion with 10 literacy discourses. The result of daily test is devided into three part, namely high, medium and low. Based on the result of daily test 13 students who get high accuracy score, 9 students in medium cluster and 8 students in low cluster. Overall students give positive responses to using Quizizz with science literacy oriented and agree to be used in the daily test. Based on students perceptions, the use of Quizizz is very interest and science literacy help them remember what they have learned.. However, there needs to be assistance from the teacher when new students use Quizizz for the first time.